A társadalomra veszélyességben való tévedés gyakorlati jelentősége a gazdasági bűncselekmények kapcsán - Mónusné Kiss, Katalin (Debreceni Jogi Műhely, 2006)
In this study I examined the error, one of the grounds for the preclusion and termination of punishability. Grounds for the preclusion of punishability and grounds for the termination of punishability, mean that punishability shall be precluded. Error, as an obstacle of the preclusion of punishability, doesn’t happened as usually as other grounds for the preclusion of punishability, for example: insane mental state, constraint and menace. The error means- 27. §- the perpetrator shall not be punishable for a fact, of which he was not aware on perpetration. The person, who commits an act in the erroneous hypothesis that it is not dangerous for society and who has reasonable ground for this hypothesis, shall not be punishable. Error shall not exclude punishability, if it is caused by negligence, and the law also punishes perpetration deriving from negligence. I examined how often the judge accept an error, if the person commit a crime, for example: tax fraud, practise usury, bribe somebody. Is it exceptional or not? When can the perpetrator of a crime refer to error? What examine judge?